Mitochondrial Enzymes of the Urea Cycle Cluster at the Inner Mitochondrial Membrane - Haskins, Nantaporn; Bhuvanendran, Shivaprasad; Anselmi, Claudio; Gams, Anna; Kanholm, Tomas; Kocher, Kristen M.; LoTempio, Jonathan; Krohmaly, Kylie I.; Sohai, Danielle; Stearrett, Nathaniel; Bonner, Erin; Tuchman, Mendel; et al. (Frontiers in Physiology, 2021)
Mitochondrial enzymes involved in energy transformation are organized into multiprotein complexes that channel the reaction intermediates for efficient ATP production. Three of the mammalian urea cycle enzymes: N-acetylglutamate synthase (NAGS), carbamylphosphate synthetase 1 (CPS1), and ornithine transcarbamylase (OTC) reside in the mitochondria. Urea cycle is required to convert ammonia into urea and protect the brain from ammonia toxicity. Urea cycle intermediates are tightly channeled in and out of mitochondria, indicating that efficient activity of these enzymes relies upon their coordinated interaction with each other perhaps in a cluster. This view is supported by mutations in surface residues of the urea cycle proteins that impair urea genesis in the patients but do not affect protein stability or catalytic activity. We find the NAGS, CPS1 and OTC proteins in liver mitochondria can associate with the inner mitochondrial membrane (IMM) and can be co-immunoprecipitated. Our in-silico analysis of vertebrate NAGS proteins, the least abundant of the urea cycle enzymes, identified a protein-protein interaction region present only in the mammalian NAGS protein - ‘variable segment’, which mediates the interaction of NAGS with CPS1. Use of super resolution microscopy showed that NAGS, CPS1 and OTC are organized into clusters in the hepatocyte mitochondria. These results implicate mitochondrial urea cycle proteins cluster, instead of functioning either independently or in a rigid multienzyme complex.